MOOC in Portuguese language teaching: a research project Portugal-Brazil - Seara, Isabel (2022)
This research proposes a theoretical-practical reflection on the aspects to be considered in the elaboration of a MOOC, destined to undergraduate and graduate students in Humanities and Linguistics. It is true that ICTs can promote more access to information and curriculum flexibility, favoring the dissemination of research and inclusion. However this practice is not very common in Brazil and in Portugal and it is still less common to take part in a MOOC. That's why we decided to create a MOOC about referencing processes, in Universidade Abertas's platform. This course is destined to undergraduate and graduate students in Humanities and Linguistics, and it is writen in Portuguese. We aim to collaborate creating a digital educacional content in these countries, and, as most of the students are also teachers, we aim to help them understand the importance of ICT in education.